Knowledge and Awareness of Basic Life Support (BLS) among Dental Students - Yoshita Guntupalli1 , K. R. Don2 , Krthik Ganesh Mohanraj3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Basic Life Support is an important life skill which should be taught to everyone. An emergency can happenat any time and any place and it is important that the people around the happening are trained to handle theemergency with utmost efficiency. This can be very helpful in reducing the number of deaths that occur. It isa must that all healthcare professionals have access to knowledge about BLS. In our study we aim to find outthe knowledge and awareness of BLS among dental students. A well structured, self-prepared questionnairewas circulated among dental students within the university of Saveetha Dental College. The students weresplit into three groups such as BDS students, Interns and MDS students. The confidence level was 95% andthe data was considered statistically significant if P value < 0.05. The results obtained were collected andanalysed to find out the awareness levels among the students and to find out which group had the highestknowledge on BLS. The data obtained was analysed and it was found that among the three groups the MDSstudents(42.86%) had the overall highest knowledge on BLS and CPR. The knowledge and awareness ofBLS among dental students was found to be moderate and not sufficient. Knowledge should definitely beimproved and more knowledge must be created.